Protein nanoparticle cellular fate and responses in murine macrophages - Ravishankar, Samyukta (2023)
Nanoparticles (NPs), both organic and inorganic, have been identified as tools for diagnostic and therapeutic (theranostic) applications. Macrophages constitute the first line of defense in the human body following the introduction of foreign antigens, including nanoparticles. However, there is a limited understanding of the cellular fate and trafficking of organic NPs in macrophages as well as the molecular responses that are triggered. This knowledge is crucial for the effective translation of these engineered molecules for theranostic applications. In this work, we performed an in-depth study on the intracellular fate and relevant immune responses of a model organic NP, Archaeoglobus fulgidus ferritin, in murine macrophage (RAW264.7) cells. Ferritin, a naturally occurring iron storage protein, has been reported to target tumors and atherosclerotic lesion sites. Herein, we demonstrate a concentration-dependent internalization mechanism and quantify the subcellular localization of ferritin NPs in various organelles. After NP exposure, export of the iron present in the ferritin core occurred over an extended period of time along with upregulation of iron-related gene mRNA expression. A study on the modulation of the intracellular localization of the NPs was conducted by incorporating peptides to mediate endosomal escape and examining their molecular effects using transcriptional analysis. To further investigate the physiological effects, we monitored the upregulation of immune-related markers (i.e., CCR2, IL1β, TNFα, VCAM-1) along with ROS generation in cells treated with ferritin under various conditions. The in-depth analyses of cellular uptake and responses to versatile protein NPs, such as ferritin, provide basic principles to design and engineer other protein NPs with similar properties for future biomedical applications.